Effect of laser remelting on the cavitation erosion behaviors of high-velocity arc-sprayed Fe-based amorphous coating in different medium - Ge Gao; Jinran Lin; Jitao Liu; Xiuqing Fu; Min Kang (Ultrasonics Sonochemistry, 2025)
In this study, high-velocity arc spraying (HVAS) technology was utilized to prepare Fe-based amorphous coating. Then, post-treatment of the coating was conducted using laser remelting (LR) technology to achieve metallurgic interfacial bonding at the coating-substrate junction. Cavitation erosion resistance of both arc-sprayed coating (ASC) and laser-remelted coating (LRC) was examined using two liquid media: distilled water and 3.5 wt% NaCl medium. The results indicated that both ASC and LRC experienced more severe cavitation erosion damage in 3.5 wt% NaCl medium compared with distilled water, demonstrating that corrosion promoted the cavitation erosion process. Notably, LRC exhibited an 77.84% lower mass loss rate than ASC in 3.5 wt% NaCl medium under cavitation erosion-corrosion conditions, indicating that the LR process effectively mitigates cavitation erosion damage despite the inherent promotion of cavitation erosion by corrosion. Furthermore, the corrosion current density (Icorr) values of ASC and LRC differed by approximate tenfold disparity under both static and dynamic cavitation conditions, indicating that LRC exhibited significantly better corrosion resistance than ASC. The enhanced cavitation erosion resistance of LRC compared to ASC primarily results from LR effectively eliminating structural defects, decreasing coating porosity from 1.73% to 0.11%, and significantly improving interfacial bonding strength. Thus, the dense and uniform microstructure enhanced the cohesive strength of the coating.